Analisis Pembelajaran Search, Solve, Create, And Share (SSCS) terhadap Peningkatan Kognisi Siswa pada Materi Tekanan di Kelas VIII MTs/SMP - Ira Azizatun Nikmah; Sinensis, Arini Rosa; Putra, Febrianto (U-Teach: Journal Education of Young Physics Teacher, 2025)
The purpose of this study is to identify student cognition after applying the Search, Solve, Create and Share (SSCS) learning model to pressure materials in grade VIII MTs Nurul Huda Sukaraja, and to determine the effect of the application of the SSCS learning model on student learning outcomes on pressure materials in grade VIII MTs Nurul Huda Sukaraja. This type of research is quantitative with the population of grade VIII students at MTs Nurul Huda Sukaraja. Sampling was carried out randomly selected for class VIII-1 and class VIII-4. The learning experiment class uses the SSCS model, while the learning control class uses the conventional learning model. Data collection techniques to determine student learning outcomes using tests and testing hypotheses using t-tests. Based on the learning outcomes of students after the test was held, the average score of the experimental class was 54.82 and the average grade of the control class was 8.54. As a result, there was a significant difference in student learning outcomes between students who used the SSCS learning model and students who used the conventional learning model. The findings of this study are that there is an effect of the application of the SSCS learning model on student learning outcomes on pressure materials in grade VIII MTs Nurul Huda Sukaraja. This can be seen from the value of tcal=8.778>ttable=0.343. So that Ho was rejected and Ha was accepted